Effects of sodium alginate and calcium on quality attributes of Shepherd’s purse under ultrasound impregnation during blanching processing - Qihui Wu; Zhongyuan Zhang; Yihong Bao; Dajing Li; Xin Wen; Lei Feng; Meimei Nie; Zhuqing Dai; Yayuan Xu (Food Production, Processing and Nutrition)
Abstract This study aimed to improve the quality of blanched Shepherd’s purse. Before blanching, Shepherd’s purse was impregnated, combined with ultrasonic treatment (US) (0, 5, 15 min) and different impregnators (calcium chloride (Ca), glucose (Gl), sodium alginate (Al)) to investigate the effects on the quality of blanched Shepherd’s purse. The contents of ascorbic acid, phenolic compounds and calcium were determined after blanching for 1 min, and the color, structure and volatile substances were analyzed. It was found that ultrasonic assisted sodium alginate impregnation for 15 min and calcium chloride treatment (Al + Ca + US15) produced very favorable effects on the quality characteristics of blanched Shepherd’s purse. Specifically, the ascorbic acid content of Al + Ca + US15 was 1.57 folds higher than that of the control group (CK), and the gallic acid and rutin content increased by 35.2% and 24.7%, respectively, compared to the CK. Additionally, the calcium content in Al + Ca + US15 was 1.27 folds higher than that in the CK. Furthermore, compared with CK, Al + Ca + US15 treatment of blanched Shepherd’s purse ΔE value was significantly reduced by 49.1%. Microstructure analysis revealed no significant difference in the internal cell space after Al + Ca + US15 treatment, and the cell morphology remained normal. In addition, the volatile data indicated that the impregnation treatment decreased the loss of volatiles after blanching. Overall, the treatment of ultrasound assisted impregnation has been found to be bio-protective for leaf vegetables when exposed to heat. Graphical Abstract